A case report of Usher's syndrome with psychosis: Challenges in diagnosis and management - Akriti Kamran; Deeksha Elwadhi; Rosali Bhoi; Mahima Malhotra (Journal of Mental Health and Human Behaviour, 2017)
Usher's syndrome is a heterogeneous autosomal recessive disorder characterized by dual sensory impairment in the form of profound congenital hearing loss and progressive visual loss due to retinal degeneration. There are only a few reports describing patients with Usher's syndrome presenting with psychotic features, and the exact etiology of its psychiatric manifestation is not clearly known. Herein, the authors report a case of Usher's syndrome with psychotic symptoms. Furthermore, the authors discuss the possible etiologies of psychotic symptoms in such cases and the challenges faced while assessing these symptoms in patients with sensory impairment.